2021
DOI: 10.3390/metabo11020120
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microbiota on the Pathogenesis of Amyotrophic Lateral Sclerosis and the Possible Benefits of Polyphenols. An Overview

Abstract: The relationship between gut microbiota and neurodegenerative diseases is becoming clearer. Among said diseases amyotrophic lateral sclerosis (ALS) stands out due to its severity and, as with other chronic pathologies that cause neurodegeneration, gut microbiota could play a fundamental role in its pathogenesis. Therefore, polyphenols could be a therapeutic alternative due to their anti-inflammatory action and probiotic effect. Thus, the objective of our narrative review was to identify those bacteria that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 180 publications
0
9
0
Order By: Relevance
“…Mediated by the gut microbiota, polyphenols were already shown to effectively attenuate AD Aβoligomerization [ 170 ] and the gut microbiota has been hypothesized as one of the potential contributions for resveratrol in mediating neuroprotection and promoting cognition. While the impact of the gut microbiota on ALS and the potential benefits of polyphenols seem promising [ 171 ], so far, no study has directly investigated them.…”
Section: Diet and Gut Microbiotamentioning
confidence: 99%
“…Mediated by the gut microbiota, polyphenols were already shown to effectively attenuate AD Aβoligomerization [ 170 ] and the gut microbiota has been hypothesized as one of the potential contributions for resveratrol in mediating neuroprotection and promoting cognition. While the impact of the gut microbiota on ALS and the potential benefits of polyphenols seem promising [ 171 ], so far, no study has directly investigated them.…”
Section: Diet and Gut Microbiotamentioning
confidence: 99%
“…In contrast, the existence of some bacteria such as Akkermansia muciniphila can have beneficial effects on ALS patients. (19,20) ALS, Amyotrophic lateral sclerosis; BMAA, Beta methyl-amino-alanine; BMI, Body mass index; Chl-a, Chlorophyll-a; EVs, Enterovirus; SD, Secchi depth; TN, Total nitrogen.…”
Section: Microbiotamentioning
confidence: 99%
“…In some studies, it was observed that transgenic mice, even at the presymptomatic stage, show evidence of dysbiosis. Among a few types of different bacteria which can be related to the pathogenesis of ALS Akkermansia muciniphila should be highlighted [54,55].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%